Cyclic strain amplitude-dependent fatigue mechanism of gradient nanograined Cu. (1st September 2020) - Pan, Q.S.; Long, J.Z.; Jing, L.J.; Tao, N.R.; Lu, L.
Abstract: Different grain coarsening behaviors (i.e. abnormal and homogeneous) are prevalently observed in gradient nanograined (GNG) Cu under stress controlled high-cycle and strain controlled low-cycle fatigue tests, respectively. In this paper, to comprehensively understand the intrinsic fatigue mechanism of gradient nanograined structures, both high and low cycle fatigue behaviors of GNG Cu are investigated under strain-controlled fatigue tests with a wide strain amplitude ranges. Cyclic behavior transition from abnormal grain coarsening at small strain amplitude to homogeneous grain coarsening at large strain amplitude is observd in GNG Cu. Microstrucural analysis reveals that the grain coarsening behavior in either abnormal or normal (homogeneous) mode is closely related to the spatial distribution of the cyclic plastic strain in the GNG layer (localized or delocalized) under cyclic loading. Such unique cyclic strain amplitude-dependent fatigue behavior is inherent to the gradient nanostructure, which fundamentally differs from the conventional strain localizing mechanism in metals with homogeneous structures under cyclic loading. Graphical abstract: Image, graphical abstract